Leitura literária no ciclo alfabetizador: repercussões das políticas educacionais no chão da escola pública municipal de Araçatuba/SP - Soares, Patrícia Cardoso (2017)
This doctoral thesis aimed to analyze how the intentions present in the institutional and pedagogical proposals, related to the implementation of practices to encourage literary reading, through the Programa Nacional Biblioteca da Escola (PNBE) and Pacto Nacional da Alfabetização na Idade Certa (PNAIC) have taken place in the period of literacy (1st to 3rd year), in the Municipal Education Services in the city of Araçatuba / SP, between the years of 2009-2016. The fragile understanding of the relevance of literary reading in the literacy cycle has led to a decrease of the importance given to the programs that propose the encouragement of this kind of reading, depriving the child of the right to aesthetic enjoyment, encouragement for the elevation of his or her level of thought and the development of literary competence, among others variants. This was a qualitative research, with exploratory approach through the analysis of the program’s development from macro to micro level, engaging 39 professionals who were on charge of monitoring and implementing the literary reading programs in Araçatuba-SP. For data collection, it was used the documental analysis, the application of questionnaires and the focus group. The investigation analysis, in the described levels, was made through Policy Cycle Approach in the context of the influence of the internationalization of educational politics. The results show elements that highlight the absence of political commitment from public officials of medium and high rank, in prioritizing the literary reading in the official curriculum, in different contexts; the need of better articulation between macro and micro level processes for analysis, understanding and adequate implementation of the policy, as well as the lack of planning of actions, by the Secretaria Municipal de Educação (SME) of Araçatuba, on what concerns the focus on literary readings